Prevalence of Allergies Due to Paracetamol Use in Children: A Literature Study - Hariaji, Ilham (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: Paracetamol is an antipyretic and analgesic drug that is often used to relieve fever and pain in children. Although considered safe, the use of paracetamol in children can cause allergic reactions. This study aims to assess the prevalence of allergies due to the use of paracetamol in children. This Literature Review identifies and analyzes articles published in the last five years, using databases such as PubMed, Scopus, and Google Scholar. The included studies were studies with cohort, cross-sectional, and case-control designs that assessed the association between paracetamol use and allergic reactions in children. Of the 23 articles that met the inclusion criteria, it was found that the prevalence of allergies due to paracetamol use in children varied between 0.1% and 6.5%. Some of the factors that play a role in increasing the risk of allergies are the history of allergies in the family and the influence of environmental factors. In addition, frequently reported types of allergies include urticaria, eczema, and anaphylactic reactions. The results of this review suggest that although the prevalence of paracetamol allergy in children is relatively low, special attention is still needed, especially in children with a history of allergies or certain medical conditions. Proper management and further understanding of the pathogenesis of paracetamol allergy in children need to be done. Allergies due to paracetamol use in children, although rare, should remain a medical concern. Further research is needed to identify clearer risk factors and to develop guidelines for the use of paracetamol in children who have allergic predispositions.